The Role of the Dopamine Transporter in Dopamine‐Induced DNA Damage - Fazeli, Gholamreza (Brain Pathol, 2010)
The neurotransmitter dopamine causes DNA damage, oxidative stress and is involved in the pathology of neurological diseases. To elucidate this potential link we investigated the mechanism of dopamine‐induced DNA damage. We studied the role of the dopamine transporter (DAT) in MDCK and MDCK‐DAT cells, containing the human DAT gene. After treatment with dopamine, only MDCK‐DAT cells showed elevated chromosomal damage and dopamine uptake. Although stimulation of dopamine type 2 receptor (D(2)R) with quinpirole in the absence of dopamine did not induce genotoxicity in rat neuronal PC12 cells, interference with D(2)R signaling by inhibition of G‐proteins, phosphoinositide 3 kinase and extracellular signal‐regulated kinases reduced dopamine‐induced genotoxicity and affected the ability of DAT to take up dopamine. Furthermore, the D(2)R antagonist sulpiride inhibited the dopamine‐induced migration of DAT from cytosol to cell membrane. To determine whether oxidation of dopamine by monoamine oxidase (MAO) is relevant in its genotoxicity, we inhibited MAO, which reduced the formation of micronuclei and of the oxidative DNA adduct 8‐oxodG. Overall, dopamine exerted its genotoxicity in vitro upon transport into the cells and oxidation by MAO. D(2)R signaling was involved in the genotoxicity of dopamine by affecting activation and cell surface expression of DAT and hence modulating dopamine uptake.